The Influence of Celebrity Endorsers and Electronic Word of Mouth (E-Wom) on Shopee Brand Trust - Dean Farrell Rayhan; Rizky Dermawan (Indonesian Journal of Business Analytics, 2023)
This research aims to explore the impact of celebrity endorser and electronic word of mouth (e-WOM) on consumer trust levels towards the Shopee brand in Surabaya city. The research method used is quantitative, involving 80 respondents selected through nonprobability sampling technique using purposive sampling method. The respondents consist of active users of Shopee marketplace aged between 15 and 40 years old. Data collection in this research involves both primary and secondary data. The analysis technique used is Partial Least Squares (PLS) with validity, reliability, and hypothesis testing. The results of the research indicate that: (1) the use of celebrity endorser has a positive and significant impact on brand trust, and (2) electronic word of mouth (e-WOM) has a positive and significant impact on brand trust.